(untitled) (Revista Internacional de Formação de Professores, 2023)
Learning is a complex process and comprises several factors related to the student, such as stimulation, motivation and cognitive organization, among others. Learning difficulties is a topic that worries teachers, families and other professionals in the area. In this sense, this text aimed to map and present studies on specific learning difficulties, published between 2012 and 2022, in Revista Educação Especial and Revista Brasileira de Educação Especial, in order to verify the trend of studies published in the referred journals. Methodologically, this is a state-of-the-art bibliographical study. Initially, we discuss the main types of specific learning disabilities (SLD) present in the literature. In the sequence, in the selection of articles in the referred journals, we applied the inclusion and exclusion criteria, with that, we identified and presented 14 articles, two of which bring in their title the terminology “learning disabilities” and the 12 others present the expressions “dyslexia”, “ADHD” or “dyscalculia”, which relate to the theme. The texts were, respectively, organized in four Tables, presenting the title, year of publication, objective and authorship. Soon after, we present the studies synthetically. In general, we conclude that, given the problem, the number of publications is low, the theme is dense and needs to be part of the menus and discussions of courses that train teachers, and that reflecting on the subject contributes to the understanding of the education inclusive process.